1998
DOI: 10.1007/s11746-998-0052-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trans fatty acids in hydrogenated vegetable oils by attenuated total reflection infrared spectroscopy: Two limited collaborative studies

Abstract: An attenuated total reflection infrared spectroscopy procedure was collaboratively studied among two sets of five laboratories for quantitating the total trans fatty acid levels in neat (without solvent) hydrogenated vegetable oils, measured as triacylglycerols in one study, and as fatty acid methyl ester derivatives in the other. Unlike the fatty acid methyl esters, the triacylglycerols required no derivatization but had to be melted prior to measurement. To obtain a symmetric absorption band at 966 cm −1 on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…This modified IR procedure (6) was also rapid (5 min) because an attenuated total reflection (ATR) liquid cell (capacity 1.5-2 mL) was used that required neither weighing nor quantitative dilution of neat melted fat test samples in any solvent. By using a single-bounce horizontal ATR cell with 50 µL capacity, this ATR IR procedure was optimized and applied to the determination of total trans fatty acids in commercial food products (11), validated in two limited collaborative studies (12), and adopted as Recommended Practice AOCS Cd 14d-97 (13). Attempts were abandoned to use a single-µL ATR cell for the quantitation of trans fatty acids in biological matrices (14,15) due to spectral interferences from conjugated fatty acids.…”
mentioning
confidence: 99%
“…This modified IR procedure (6) was also rapid (5 min) because an attenuated total reflection (ATR) liquid cell (capacity 1.5-2 mL) was used that required neither weighing nor quantitative dilution of neat melted fat test samples in any solvent. By using a single-bounce horizontal ATR cell with 50 µL capacity, this ATR IR procedure was optimized and applied to the determination of total trans fatty acids in commercial food products (11), validated in two limited collaborative studies (12), and adopted as Recommended Practice AOCS Cd 14d-97 (13). Attempts were abandoned to use a single-µL ATR cell for the quantitation of trans fatty acids in biological matrices (14,15) due to spectral interferences from conjugated fatty acids.…”
mentioning
confidence: 99%
“…Studies assessed accuracy, repeatability and reproducibility in the analysis of trielaidin and methyl elaidate standards, refined oil and partially hydrogenated vegetable oils (PHVO), and oils spiked with trielaidin [35,36]. Repeatability and reproducibility are suitable for middle or high TFA levels, but decrease when TFA amounts approach the quantification limit (1% TFA as % total FA).…”
Section: Atr-ftir Spectrometrymentioning
confidence: 99%
“…By using this 50-µL cell, two collaborative studies were conducted (8) in each of five laboratories on neat triacylglycerols (TAG) and the corresponding neat FAME derivatives. The lower limit of trans quantitation was about 1% of total fat.…”
mentioning
confidence: 99%
“…The lower limit of trans quantitation was about 1% of total fat. Because it was demonstrated that the "ratioing" and ATR procedure was an acceptable alternative for the IR determination of the total trans fatty acid content (6)(7)(8)(9), it was adopted as Recommended Practice Cd 14d-96 by AOCS in 1996 (10). Recently, it was used by Sedman et al (11) as a reference method to validate a proposed transmission IR procedure.…”
mentioning
confidence: 99%
See 1 more Smart Citation